2003
DOI: 10.1377/hlthaff.22.3.134
|View full text |Cite
|
Sign up to set email alerts
|

Public Reporting On Quality In The United States And The United Kingdom

Abstract: PROLOGUE:Report cards represent one of the most publicly visible aspects of hospitals' quality improvement efforts, and they are not without controversy. Media coverage often overreacts to low "grades" given to hospitals in a region. Providers find ways to stack the decks, selecting the healthiest patients to improve their scores. Purchasers look only at costs, and consumers either can't figure them out or ignore them completely. At least, this is the popular perception. The need for basic research to develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
169
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(175 citation statements)
references
References 33 publications
1
169
0
2
Order By: Relevance
“…Consistent with prior research, only a small minority reported comparing the quality of hospitals. 18 Employees who chose the lower-deductible CDHP in 2004 consistently reported the greatest use of health-related information in the prior year. They were more likely to have used a Web site or book for health information or how to handle a symptom or health problem.…”
Section: Study Findingsmentioning
confidence: 96%
“…Consistent with prior research, only a small minority reported comparing the quality of hospitals. 18 Employees who chose the lower-deductible CDHP in 2004 consistently reported the greatest use of health-related information in the prior year. They were more likely to have used a Web site or book for health information or how to handle a symptom or health problem.…”
Section: Study Findingsmentioning
confidence: 96%
“…Public reporting of patient experience in combination with an array of interventions that take in to consideration the context of a healthcare system may have greater potential to stimulate providers to improve quality [51][52][53]. Although public reporting may encourage improvements through increased competition between health providers and professionals, a review exploring the impact of public reporting of patient experience, in combination with patient outcomes (such as mortality rates in hospital wards), found that some surgeons became more reluctant to care for highrisk patients (e.g.…”
Section: How Can Patient Experience Data Be Usedmentioning
confidence: 99%
“…The goal is not an exhaustive review of the literature, but rather to demonstrate that both desired and unintended consequences have been observed following prior public-report release. [The reader is referred to recent reviews of the literature on public reporting for more detailed assessments of the history of positive and negative effects of public reports on overall quality by Marshall et al (26,27) and Werner & Asch (45).] Evidence of prior benefit and/or harm resulting from public reporting does not necessarily predict the magnitude of the impact of present and future reports, given current and expected progress in public-reporting design and implementation.…”
Section: Has Public Reporting Changed Hospital Quality Of Care?mentioning
confidence: 99%